2009
DOI: 10.1086/599782
|View full text |Cite
|
Sign up to set email alerts
|

Mapping School Segregation: Using GIS to Explore Racial Segregation between Schools and Their Corresponding Attendance Areas

Abstract: We examine whether student enrollment in nonneighborhood schools changes levels of racial segregation in public schools across urban school districts by comparing the racial composition of schools and their corresponding attendance area. This comparison was made possible by using geographic information systems (GIS) to link maps of elementary, middle, and high school attendance boundaries with 2000 census data, the Common Core of Data, and the Private School Survey for the 22 largest school districts. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
67
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 28 publications
0
67
0
1
Order By: Relevance
“…In Equation 1, the manner of defining an appropriate choice set plays a decisive role in explaining what features stimulate individual EMOs to get involved in a particular market, which is expected to allow the maximization of profits. Some studies establish potential choice sets within a given mile radius from homes (Bell, 2009;Burgess, Greaves, Vignoles, & Wilson, 2011;Cobb & Glass, 1999), and a number of scholars identify a charter school's catchment area as the Census geographic units and school attendance boundaries to which the charter school belongs (Garcia, 2008;Ritter, Jensen, Kisida, & Bowen, 2016;Saporito & Sohoni, 2006;Sohoni & Saporito, 2009). Even though these technical approaches may be a simple and convenient method, they have impeded the progress of research on access to charter schools with non-residence requirements in competitive markets.…”
Section: Market Density In Site Selectionmentioning
confidence: 99%
“…In Equation 1, the manner of defining an appropriate choice set plays a decisive role in explaining what features stimulate individual EMOs to get involved in a particular market, which is expected to allow the maximization of profits. Some studies establish potential choice sets within a given mile radius from homes (Bell, 2009;Burgess, Greaves, Vignoles, & Wilson, 2011;Cobb & Glass, 1999), and a number of scholars identify a charter school's catchment area as the Census geographic units and school attendance boundaries to which the charter school belongs (Garcia, 2008;Ritter, Jensen, Kisida, & Bowen, 2016;Saporito & Sohoni, 2006;Sohoni & Saporito, 2009). Even though these technical approaches may be a simple and convenient method, they have impeded the progress of research on access to charter schools with non-residence requirements in competitive markets.…”
Section: Market Density In Site Selectionmentioning
confidence: 99%
“…However, some authors have found that charter schools increase racial segregation (Bifulco & Ladd, 2007) and the potential to further stratify schools along racial and socioeconomic profiles, allowing a mechanism to escape racial integration (Cobb & Glass, 1999). Sohoni and Saporito (2009) examine levels of racial segregation in private, charter, and magnet schools. Their results show that "public schools would be less racially segregated if all children living in a school district attended their local, neighborhood schools.…”
Section: Preferences For Race/ethnicity and The Socioeconomic Composimentioning
confidence: 99%
“…For example, Bifulco and Ladd (2007) found that charter schools enroll a disproportionately high percentage of African-American students compared to public schools. Sohoni and Saporito (2009) also found that higher percentages of White children attend schools of choice than non-White children. Lastly, teacher compensation is often different between private, public, and charter schools and most definitely affects teachers' decisions to stay or leave their school.…”
Section: Scope Of the Study And Delimitationsmentioning
confidence: 86%